Accuracy Meets Interpretability for Computational Spectroscopy by Means of Hybrid and Double-Hybrid Functionals - Barone, Vincenzo; Ceselin, Giorgia; Fusè, Marco; Tasinato, Nicola (Frontiers in Chemistry, 2020)
Accuracy and interpretability are often seen as the devil and holy grail in computational spectroscopy and their reconciliation is still a primary research goal. In the last decades, density functional theory has revolutionized the situation, paving the route towards reliable yet effective models for medium size molecules, which could be profitably used also by non specialists. In this contribution we will compare the results of several widely used hybrid and double hybrid functionals with the aim of defining the most suitable recipe for all the spectroscopic parameters of interest in rotational and vibrational spectroscopy going beyond the rigid rotor/harmonic oscillator model. We will show that last-generation hybrid and double hybrid functionals in conjunction with partially augmented double- and triple-zeta basis sets can offer, in the framework of second order vibrational perturbation theory, a general, robust and user-friendly tool with unprecedented accuracy for medium-size semi-rigid molecules.